Giant bleeding post-traumatic thoracic sarcoma management: A case report - Shabunin, Alexey V; Lebedinsky, Ivan N; Dolidze, David D; Bagatelia, Zurab A; Covantsev, Serghei; Bocharnikov, Dmitry S; Gogitidze, Nodar N (Frontiers in Surgery, 2022)
The heterogeneity of thoracic wall tumors often represents challenging clinical entities for surgeons due to diagnostic and treatment complexities. The primary tumors, metastases, or direct invasion from intrathoracic structures comprise almost half of all cases on average that are proved to be malignant. Surgery treatment usually leaves large chest defects that require further extensive reconstruction and multimodal management including radiotherapy and chemotherapy. We report a rare case of a giant (30 cm) post-traumatic bleeding thoracic sarcoma treatment in a 70-year-old female. The use of our modified Verneuil technique to close the extensive postoperative skin defect optimized surgical wound management and provided good functional and aesthetic results. Four-year follow-up outcomes after surgical and adjuvant radiation therapy reported a high level of tumor control and showed no evidence of postoperative disease recurrence.